Internet Sales Channel and Manufacturers’ Brand: A Transaction Cost Analysis - Asmat-Nizam Abdul-Talib; Ng Hong Teong (International Journal of Supply Chain Management, 2019)
In modern age, Internet has brought massive impact to the distribution channel management. Especially to the manufacturers, harnessing the power of Internet is deemed a strategic step to reinforce the products' awareness among consumers and further improve market share. However, the outcomes of setting up Internet sales channel are mixed. Although some organizations do exemplify the success of online sales channel, there are manufacturers who simply fail in this aspect. This paper aims to provide insights into the factors which manufacturers must take into consideration in contemplating to setting up Internet sales channel. By using transaction cost analysis (TCA), we set up a research model, which composed of various factors which are critical to the success of Internet sales channel and elaborate the role of these factors on this issue. Subsequently, appropriate propositions are instigated and investigated in order to determine the impact of these variables on the manufacturers’ decision making in this area.